PEMIKIRAN PENDIDIKAN IBNU KHALDUN DAN RELEVANSINYA TERHADAP PEMBELAJARAN SAINS DI MADRASAH IBTIDAIYAH - Karim, Siti Ruqoiyyah (Alifbata : Jurnal Pendidikan Dasar, 2022)
This study aims to describe the concept of science education in Madrasah Ibtidaiyah that is expected at this time, the educational model according to Ibnu Khaldun, the goals of education according to Ibnu Khaldun and its relevance to Science education in Madrasah Ibtida'iyah. This type of research is Library Research with the primary data source from the work of Ibn Khaldun, namely the Muqqaddimah Book, and the secondary data source is obtained from books, journals and other writings related to science education in Madrasah Ibtidaiyah and Ibn Khaldun's educational thoughts. Data collection techniques by identifying information from books, previous research reports, journals, articles, the web, or other information. This research uses descriptive analysis method. The results of this study indicate that science education in Madrasah Ibtidaiyah is directed through direct experience, scientific investigations develop process skills and scientific attitudes, 2) according to Ibnu Khaldun education is a process of consciously capturing, absorbing and experiencing natural events throughout the ages. 3) The similarity of the educational model of Ibnu Khaldun with science education in elementary schools, namely in the teaching method which does not force students to memorize and requires students to be actively involved in the learning process, 4) The relevance between the two is in concept, purpose, position of educators and students.